Response of Dendritic and NK Cells After Multispecies Probiotic Administration in BALB/C Mice - Andy Darma, - (North University of Baia Mare, 2019)
Dendritic and Natural killer (NK) cells play important roles in the innate immune response. The administration of probiotics is known to affect the immune response. The study aims to assess the effects of multiple probiotic species on the activities of dendritic and NK cells after gastrointestinal damage induced by bacterial lipopolysaccharide (LPS). Male Balb/c mice (n=24) were randomized into four groups: the K-I group (LPS and probiotics), K-II group (LPS only), K-III group (probiotics only), or K-IV group (no intervention). LPS was produced by Escherichia coli O5:B55 cells, while the probiotics were a combination of Lactobacillus acidophilus PXN 35, L. casei subsp. casei PXN 37, L. rhamnosus PXN 54, L. bulgaricusPXN 39, Bifidobacterium breve PXN 25, B. infantis PXN 27, and Streptococcus thermophilus PXN 66. LPS was administered on day 15, while probiotics were administered for 21 consecutive days. After 21 days, the mice were sacrificed and the numbers of dendritic and NK cells were determined by immunohistochemical staining of the ileum. Comparisons with the independent samples t-test showed that as compared to the control group, probiotic administration had significantly increased the numbers of dendritic cells, but not NK cells. Meanwhile, in the presence of LPS, there was a significant difference in the number of dendritic cells between the probiotic-LPS and the LPS only groups, but not NK cells. Multiple probiotic species can regulate the innate immunity response through dendritic cells, but not NK cells, in Balb/c mice.